Peningkatan Nilai Tambah Pada Agroindustri Manggis Melalui Pengembangan Produk Teh dan Sirup Berbasis Kulit Manggis - Santosa, Santosa; Derosya, Vioni; Asben, Alfi; Azrifirwan, Azrifirwan; Permata, Deivy Andhika; Fiana, Risa Meutia; Kasim, Fitriani; Neswati, Neswati; Ismanto, Sahadi Didi; Dewi, Kurnia Harlina; Rahmi, Ira Desri; Yulianto, Kiki; Putri, Annisa; Rahayu, Lisa; Saputra, Hendra; Rozalia, Rozalia; Sari, Dini Novita (PATRIOTIKA: Jurnal Inovasi dan Pemberdayaan Masyarakat, 2025)
Limau Manis Village as Kampung Manggis is supported by the production of mangosteen in Padang City which is number 2 (two) in West Sumatra and 80% of mangosteen in Padang City comes from Pauh Subdistrict, with the center being in Limau Manis Village and the existence of Kampung Manggis brings hope for the community to improve their economy and will have an impact on the economy of the Padang City community. The skin of mangosteen fruit can be processed into value-added products. However, farmers and local businesses still face several challenges, such as the lack of knowledge and technology to process mangosteen peels into economically valuable products. Abundant mangosteen peels during the harvest season are often discarded or burned, causing environmental impacts such as soil and air pollution. However, due to the lack of public knowledge on mangosteen peel processing as waste, an innovative solution is needed to turn mangosteen peel waste into a new source of income through the development of competitive derivative products. This community service activity is designed as a strategic step to empower the community, optimize local potential, and build an innovative, sustainable mangosteen agroindustry, creating value-added products and improving the economic welfare of the community. In addition, this activity is also expected to be a model of agroindustry development based on local potential that can be developed. The purpose of this community service activity is to provide training in improving the knowledge, skills of the community in processing mangosteen skin, increasing the added value of mangosteen skin into mangosteen skin tea and mangosteen skin syrup products that have a broad impact on economic, social and environmental improvement.